Improving the Quality of Life for the Elderly Group through Basic Financial Literacy Education Program - Chorry Sulistyowati; Made Gitanadya Ayu Aryani; Zahrin Hasnina Qalby (Jurnal Pengabdian Masyarakat, 2023)
Purpose: This research paper explores the significance of enhancing financial literacy among the elderly. It focuses on a community program in Gundih Village, Surabaya, conducted in August 2022, aiming to improve the elderly's quality of life through primary financial education. Method: The study employed a comprehensive approach, including workshops and assessments to teach critical financial concepts. Data was collected through surveys, interviews, and observations analyzed quantitatively and qualitatively to gauge the program's impact. Practical Applications: The study's findings have practical implications. By equipping the elderly with financial knowledge, particularly in retirement planning, savings, and loans, the program empowers them to make informed financial decisions, reducing potential burdens on their families. Conclusion: This research underscores the importance of financial literacy for the elderly. The program in Gundih Village serves as a successful model, demonstrating that improving financial knowledge enhances the elderly's financial independence, benefiting both them and their families.